A study analysis of student attitude to science lessons - Tanti Tanti; Dwi Agus Kurniawan; Lika Anggraini; Rahmat Perdana (Journal of Education and Learning (EduLearn), 2020)
An attitude is a form of one's perception of an object that is described with expressions of like or not. The purpose of the study was to describe the attitudes of students towards the three indicators of the attitude of the junior high school in Batanghari. The research method uses quantitative survey research. The instrument used was a questionnaire that focused on three indicators consisting of 18 statements and also interviews. The sample in this study was 280 students in Batanghari. The results of research on three attitude indicators which became the dominant focus of research in the good category. The Social Implications of the Science show a good category with a percentage of 57.9%. The pleasure of science learning is well categorized with a percentage of 45.4%. The attitude towards the science investigation is categorized sufficiently with the percentage category of 41.1%. From the research that has been carried out, it can be seen that the attitude of students in junior high school is categorized as good, because the three indicators examined show good categories.